Implementation of Innovative Learning Method of Business Practice Teaching Firms to Grow Entrepreneurship Characters - Widyaningrum, Bakti; Surindra, Bayu (Dinamika Pendidikan, 2017)
The research aim to implement innovative learning methods of business practice teaching firm’s to cultivate students entrepreneurial character. Intellectual unemployment in 2016 has increased significantly compared to the previous year. Intellectual unemployment is unemployment delivered by college graduates. Therefore, universities should be able to organize innovative learning to be able to deliver their graduates with entrepreneurship character. This is a development research applying a learning method rather than proving a theory. The subjects of the study were Mathematics Education students who take entrepreneurship courses amounting to 38 students. The innovative learning method used is Business Practice Teaching Firms (BPTF) that emphasizes learning on learning by doing process with entrepreneurship practices that are made as closely as possible with real companies. By using descriptive analysis, it is found that entrepreneurship characters is initiative, self-confidence, being able to take risks and turn to behave, being able to control situation, innovative and creative, and having leadership spirit that may increase after BPTF has been applied in the learning process.